Naive and Effector B-cell Subtypes are Increased in Chronic Rhinosinusitis with Polyps. Issue 1 (January 2018) - Miljkovic, Dijana; Psaltis, Alkis; Wormald, Peter-John; Vreugde, Sarah
Background: Recent studies demonstrated that B cells and their chemoattractants are elevated in the nasal mucosa of patients with chronic rhinosinusitis (CRS) with nasal polyposis (CRSwNP). However, the presence of naive B cells and of plasmablasts and memory B-cell subsets in the mucosa and periphery of the same patient with CRS is yet to be characterized. Objective: Here we sought to quantify naive, plasmablasts, and memory B cells in mucosal tissue and peripheral blood of patients with CRSwNP, patients with CRS without nasal polyps (CRSsNP), and control patients. Methods: Polyps, mucosa, and peripheral blood samples were prospectively collected from the patients with CRS and from the non-CRS controls. We used flow cytometry to distinguish among naive, plasmablast, and memory B cells in sinus tissue and peripheral blood. Results: A total of 45 patients were recruited for the study. The patients with CRSwNP had significantly increased mucosal B-cell numbers versus the controls (3.39 ± 4.05% versus 0.39 ± 1.05% of live cells; p < 0.01, Kruskal-Wallis test), which included naive B cells (0.61 ± 0.94 versus 0.11 ± 0.24% of live cells; p < 0.03, Kruskal-Wallis test), plasmablasts (0.06 ± 0.26 versus 0.00 ± 0.00% e cells; p < 0.055, Kruskal-Wallis test), and memory B cells (0.62 ± 1.26 versus 0.05 ± 0.15% of live cells; p < 0.02, Kruskal-Wallis test). Conclusion: Our study identified increased frequencies of different B-cell subtypes in the mucosa of patients with CRSwNP but not in the peripheral blood. We also found that patients with CRSwNP had significantly increased B-cell subtypes compared with the patients with CRSsNP and the controls. These results implied a potential role for mucosal B cells in the ongoing inflammation in patients with CRSwNP.